Early Inhibition of Activated Fibrinolysis Predicts Microbial Infection, Shock and Mortality in Febrile Medical Patients - Raaphorst, Joost; Groeneveld, A. B. Johan; Bossink, Ailko W. J.; Hack, C. Erik (Thrombosis and Haemostasis, 2001)
To evaluate the contribution of an imbalance between coagulation activation and fibinolysis activation and inhibition to morbidity and mortality in sepsis, we determined in medical hospitalized patients at inclusion (day 0) for fever (temperature above 38.0° C axillary or 38.3° C rectally), and daily thereafter for two days, circulating thrombin-antithrombin III (TAT) complexes, plasmin- 2-antiplasmin (PAP) complexes (day 0 only), tissue-type plasminogen activator (t-PA), plasminogen activator inhibitor-1 (PAI-1) and interleukin (IL)-6, the latter as a marker of the inflammatory host response. Study variables were 1) positive microbiological results for specimens from local sites associated with a clinical infection, positive blood cultures (including parasitemia) or both, within 7 days after inclusion, 2) development of shock, i.e. systolic blood pressure <90 mmHg or a reduction of 40 mmHg from baseline within 7 days after inclusion, and 3) death related to febrile illness within 28 days after inclusion. The peak plasma levels of TAT complexes were elevated in 44% and the PAP complexes in all patients. The t-PA and PAI-1 levels were elevated in 74 and 94% of patients, respectively. Values for TAT and PAP did not differ among subgroups, while peak t-PA and IL-6 levels were higher in patients with positive microbiological results, developing shock or ultimately dying than in those without the complications (p <0.005). Peak PAI-1 levels were elevated in patients developing shock and ultimate death versus those with an uncomplicated course (p <0.05). Peak IL-6 related to PAI-1 and t-PA levels, which interrelated. Patients with elevated TAT levels had increased plasma levels of IL-6, PAP, PAI-1 and t-PA versus those with normal TAT (p <0.05). Our data indicate that inhibition of activated fibrinolysis, which may partly depend on both cytokinemia and activation of coagulation, predicts microbial infection, septic shock and mortality of febrile medical patients. This suggests an early pathogenic role of inhibition of activated fibrinolysis in the downhill course of serious microbial infection.
Keywords: Fever; coagulation; fibrinolysis; septic shock; death; PAI-1; t-PA; TAT